Division of the spinal accessory nerve in the anterior triangle: a prospective clinical study. Issue 7 (September 2015) - Brennan, P.A.; St J. Blythe, J.; Alam, P.; Green, B.; Parry, D.
Abstract The anatomical relation between the spinal accessory nerve and internal jugular vein is well documented, but other variants of the nerve, including the contributions of the cervical plexus to supply motor fibres to the trapezius, are less well known. We have previously described an anatomical variant in which the spinal accessory nerve divided before entering the sternocleidomastoid, and the inferior trunk passed directly under it to supply the trapezius. We now present a prospective study of 133 neck dissections (excluding radical dissections) in which a meticulous search was made for the variant in the anterior triangle of the neck during operation. We found it in 3 necks (2%). One of the 3 patients had a bilateral neck dissection but it was found on one side only, and in 2 cases it communicated with the cervical plexus. In all 3, stimulation of the inferior division resulted in contraction of the trapezius while the upper division was found to supply the sternocleidomastoid only. The finding of this variant, which was more common than first thought, highlights the need for meticulous dissection of the nerve before it enters the sternocleidomastoid to ensure that, when present, the inferior branch is preserved to minimise potential postoperative shoulder dysfunction. Further research including a cadaveric study is needed to understand this important variant more fully.